Islamic State: Unveiling Abu Ala Maududi’s Divine Sovereignty and Political Vision in Colonial India. - Rameez Ahmad Lone (UIN Sunan Gunung Djati, 2024)
This research scrutinizes Abu Ala Maududi's pivotal thesis on the Islamic State (IS), encompassing its theological underpinnings, contextual genesis, and organizational structure. This study evaluates Maududi's justification of the state by examining key Quranic principles and his reinterpretation of fundamental terms. It contrasts his model with Western democracy, emphasizing its ideological and monolithic nature. This research explores Maududi's nuanced governance approach, legislative bodies, and the role of non-Muslims in the Islamic State. Facing rejection, Maududi aligned his vision with the political shifts in colonial India. The article acknowledges ongoing scholarly discourse and underscores the lasting impact of Maududi's Islamic State thesis, providing a comprehensive understanding of its multifaceted vision in the interconnection between theology, politics, and governance.